Lack of phototoxicity potential with delafloxacin in healthy male and female subjects: comparison to lomefloxacin. Issue 6 (3rd May 2018) - Dawe, R. S.; Ferguson, J.; Ibbotson, S.; Lawrence, L.; Paulson, S.; Duffy, E.; Cammarata, S.
Abstract : Aims : Delafloxacin is a fluoroquinolone antibiotic recently approved by the FDA for treatment of acute bacterial skin and skin structure infections (ABSSSI). Abstract : Aims : Delafloxacin is a fluoroquinolone antibiotic recently approved by the FDA for treatment of acute bacterial skin and skin structure infections (ABSSSI). Delafloxacin was assessed for phototoxicity potential compared with a known phototoxic fluoroquinolone. Methods : A Phase 1, investigator-blind, placebo/active-controlled, randomized, parallel-group study was conducted in 52 healthy male and female volunteers who received 200 or 400 mg of oral delafloxacin, 400 mg oral lomefloxacin or placebo once daily for 6 days. This study evaluated the photosensitizing potential and possible wavelength dependency of delafloxacin by comparing the response of the skin to ultraviolet A (UVA), ultraviolet B (UVB) and visible radiation prior to and during administration of delafloxacin, lomefloxacin as a positive control, or placebo. Adverse events were monitored throughout the study. Results : Forty-seven subjects completed six days of dosing, and no evidence of phototoxicity was seen with delafloxacin. Delafloxacin at 200 and 400 mg day −1 and placebo did not demonstrate differences in percent change from baseline in minimal erythema dose at all tested wavelengths (295–430 nm) by monochromator and solar simulator. Lomefloxacin, the positive control, had statistically significant differences ( p < 0.05) at UVA wavelengths of 335 and 365 ± 30 nm 24 hours after radiation exposure (maximum response). The phototoxic index results were significantly higher for lomefloxacin at 335 nm and 365 nm compared to placebo and delafloxacin. Conclusions : 200 and 400 mg of delafloxacin administered for 6 days were well tolerated in healthy adult volunteers. Delafloxacin and placebo failed to demonstrate a phototoxic effect but lomefloxacin, the positive control, demonstrated moderate phototoxicity.